Managing high-technology programs and projects - Archibald, Russell Dean (Wiley, 2003)
This book fulfills a long-standing need for a comprehensive, practical and unified description of the business of managing complex programs and projects. It provides detailed coverage of all aspects of complex project management, with emphasis on those involving advanced technology